STRATEGI SEGMENTASI WAJIB PAJAK KENDARAAN BERMOTOR DAN BBNKB DALAM UPAYA MENGOPTIMALKAN PAD - Priancaya, Putu; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 9 No 3 (2014), 2014)
Local tax and local retribution are local income sources. It is an original local government that have authority to conduct pick up and management of vehicle tax (PKB) and tax to transfer ownership (mutation) especially acceptance of tax for this result, it is one of potencial acceptance source in order to improve local income at each regency level or city. Amount of PKB acceptance and BBNKB as tax acceptance source for the result can be said significant for Denpasar city. But this amount not yet standard to conduct monitoring and evaluation of tax payer, especially from PKB and BBNKB taxpayer either individually or corporation. Remind of traffic access have been not adequate. The study aims to find out of strategy for PKB and BBNKB segmentation in optimalization of local tax (PAD) acceptance of Denpasar city.This study was used case study, and using descriptive qualitative approach. Object in this study were local origin income (PAD), vehicle tax (PKB) and Mutation tax (BBNKB) in Denpasar city. This study were used primary and secondary data. Technique of data analysis was used descriptive qualitative. The result shows that the strategy can be conducted by the local government in this case, the income service as the authority to pick up the tax through Samsat (UPTD) Denpasar can improve acceptance of PKB and BBNKB through (1) Tightening of sanction, (2) improve of tax administration system.
Keywords: Local Origing Tax (PAD), Strategy, PKB, BBNKB